The Musi Board as a didactic tool: strengthening conceptual mastery of greatest common factor and least common multiple - Kusumawati, Sri Silvia; Darmawan, Puguh (Polyhedron International Journal in Mathematics Education, 2025)
This study employed a qualitative case study approach to investigate the effectiveness of the Musi board in enhancing students’ understanding of the abstract mathematical concepts of Greatest Common Divisor (GCD) and Least Common Multiple (LCM). These topics were often difficult for students due to their abstract nature and the limited use of concrete learning media. The participants were third-semester students from Offering E in the Mathematics Department at Universitas Negeri Malang. The learning process was conducted using the Problem-Based Learning (PBL) model, where the Musi board functioned as both a visual aid and a tool for collaborative problem solving. The teaching sequence followed five PBL stages: problem orientation, student organization, guided investigation, group presentation, and evaluation. Data collection included classroom observations, video recordings, student worksheets (LKPD), and written feedback from the course lecturer. The data were analyzed using Miles and Huberman’s interactive model consisting of data reduction, data display, and conclusion drawing. The findings revealed that the Musi board helped students concretize abstract mathematical ideas, making it easier to grasp and apply GCD and LCM concepts in problem-solving contexts. It also encouraged active participation and collaborative learning. The implication of this research was that integrating simple, culturally relevant, and interactive media like the Musi board into mathematics instruction could significantly improve conceptual understanding. Teachers were encouraged to incorporate such tools into their practice to make abstract content more accessible and engaging for students.